The string quartets of Béla Bartók tradition and legacy in analytical perspective - Biró, Dániel Péter 1969-; Krebs, Harald 1955- (Oxford University Press, 2014)
At the centre of Bartók's uvre are his string quartets, which are generally acknowledged as some of the most significant pieces of 20th century chamber music. This book examines these remarkable works from a range of theoretical and methodological perspectives.
Keywords: Bartók, Béla -- 1881-1945; String quartets / Analysis, appreciation; Musikalische Analyse; Streichquartett; Aufsatzsammlung